Cabazitaxel inhibits proliferation and potentiates the radiation response of U87MG glioblastoma cells. (14th February 2018) - Neshasteh‐Riz, Ali; Zeinizade, Elham; Safa, Majid; Mousavizadeh, Kazem
Abstract: Cabazitaxel is a second‐generation semisynthetic taxane. The recognized anti‐neoplastic effect of Cabazitaxel is cell cycle perturbation by inducing arrest at G2/M. Since glioblastoma tumors have a relatively high expression of P‐gp, it is encouraging to find a treatment that is effective against these tumors. This study was conducted to examine the radiosensitizing potential of Cabazitaxel against U87MG cells. In order to evaluate the effect of Cabazitaxel, cells were treated with different concentrations of the drug at different time intervals and then cytotoxicity and cell cycle were assessed using MTT and flow cytometry assays, respectively. Annexin/PI and real‐time polymerase chain reaction (PCR) assays were used to evaluate the extent of apoptosis. Cabazitaxel exerted a consistent G2/M arrest and resulted in a concentration‐ and time‐dependent toxicity. Cabazitaxel enhanced the cytotoxicity response of U87MG cells to radiation. Apoptosis increased following Cabazitaxel‐IR administration. At the same time, these results were further supported by apoptotic genes regulation. This study provides the first preclinical evidence supporting that Cabazitaxel can render U87MG cells more susceptible to the cytotoxicity of radiation and could potentially be administered in combination modalities as a promising cell cycle‐specific radiosensitizer for the future steps of in vivo evaluation.